Individual differences and cognitive reflection across gender and nationality the case of the United Arab Emirates - Ray Saadaoui Mallek; Mohamed Al-Baity (Cogent Economics & Finance, 2019)
This study aims to investigate the effect of gender differences and nationality on the Cognitive Reflection Test (CRT), as well as behavioural biases. A sample of 770 questionnaires was collected from undergraduate business students in public and private universities across the United Arab Emirates. The results suggested that low CRT values were dominant in males and females alike for non-UAE citizens in the age group of 18-22 years old, of whom at least one of the parents had a college degree. Subjects with higher cognitive reflection scores were significantly more likely to exhibit overconfidence, risk preference, and risk illiteracy. In addition, females scored lower than males, and non-UAE citizens scored higher than local citizens in the CRT. However, further analysis of the interaction between gender and nationality revealed that local females scored on average higher than non-UAE females.
Keywords: 330; Cognitive Reflection Test; gender effects; dual processes; risk literacy; risk preference